PRAKTIK PENGOBATAN ALTERNATIF DALAM PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN DI INDONESIA - Anak Agung Rai Gayatri Artha Yani; I Nyoman Gede Sugiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
The efforts of each community in maintaining health for themselves are very diverse. Generally, people use alternative medicine health services because of the relatively low cost, but there are still many business actors from alternative medicine who open practices arbitrarily without having a business license. This is because there are still not many regulations or standardization regulated in legislation regarding alternative medicine practices that harm consumers. The problem formulations in this study, namely: 1). How the regulation of alternative medicine practices in legal settings has positive effects in Indonesia; 2) How is the form of legal protection for consumers in alternative medicine practices in Indonesia. The method used in this research is the type of normative legal research with the type of statutory approach and conceptual approach. Through this research, it can be determined that the regulation of alternative medicine is contained in Law Number 36 of 2009 concerning Health. If consumers suffer losses due to the actions of business actors, they can be given protection through Law Number 8 of 1999 concerning Consumer Protection, which forms of protection are divided into preventive legal protection and repressive legal protection.